Specyficzne metody dydaktyczne dotyczące procesów poznawczych w nauczaniu literatury = Specific didactic methods concerning the cognitive processes in teaching literature - Grzesik, Jürgen (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article consists of two parts. The first more theoretic part based on opinions of such scholars as Humboldt, Iser, Ingarden, Mauser, Morris, Wygotski and Ausubel, contains considerations about the formation of layers of schematized aspects and opinions of readers in the course of reception of a literary work. The second part refers directly to didactic lessons and shows different phases and ways of shaping opinions on the base of a literary text.
Keywords: literatura; nauczanie; procesy poznawcze; metodyka